Fake news reminders and veracity labels differentially benefit memory and belief accuracy for news headlines - Paige L. Kemp; Vanessa M. Loaiza; Christopher N. Wahlheim (Scientific Reports, 2022)
Abstract Fake news exposure can negatively affect memory and beliefs, thus sparking debate about whether to repeat misinformation during corrections. The once-prevailing view was that repeating misinformation increases its believability and should thus be avoided. However, misinformation reminders have more recently been shown to enhance memory and belief accuracy. We replicated such reminder benefits in two experiments using news headlines and compared those benefits against the effects of veracity labeling. Specifically, we examined the effects of labeling real news corrections to enhance conflict salience (Experiment 1) and labeling fake news on its debut to encourage intentional forgetting (Experiment 2). Participants first viewed real and fake news headlines with some fake news labeled as false. Participants then saw labeled and unlabeled real news corrections; labeled corrections appeared alone or after fake news reminders. Reminders promoted the best memory and belief accuracy, whereas veracity labels had selective effects. Correction labels led to intermediate memory and belief accuracy, whereas fake news labels improved accuracy for beliefs more than memory. The extent that real and fake news details were recalled together correlated with overall memory and belief differences across conditions, implicating a critical role for integrative encoding that was promoted most by fake news reminders.